Anisotropic Band-Edge Absorption of Millimeter-Sized Zn(3-Ptz)2single-Crystal Metal-Organic Frameworks - Cardenas-Jiron, G; Herrera-Urbina, F; Singh, D; Urzua-Leiva, R; Fritz, R; Chi-Duran, I (American Chemical Society, 2022)
Metal-organic frameworks (MOFs) have emerged as promising tailor-designed materials for developing next-generation solid-state devices with applications in linear and nonlinear coherent optics. However, the implementation of functional devices is challenged by the notoriously difficult process of growing large MOF single crystals of high optical quality. By controlling the solvothermal synthesis conditions, we succeeded in producing large individual single crystals of the noncentrosymmetric MOF Zn(3-ptz)2(MIRO-101) with a deformed octahedron habit and surface areas of up to 37 mm2. We measured the UV-vis absorption spectrum of individual Zn(3-ptz)2single crystals across different lateral incidence planes. Millimeter-sized single crystals have a band gap of Eg= 3.32 eV and exhibit anisotropic absorption in the band-edge region near 350 nm, whereas polycrystalline samples are fully transparent in the same frequency range. Using solid-state density functional theory (DFT), the observed size dependence in the optical anisotropy is correlated with the preferred orientation adopted by pyridyl groups under conditions of slow crystal self-assembly. Our work thus paves the way for the development of optical polarization switches based on metal-organic frameworks. © 2022 American Chemical Society. All rights reserved.